Logistics, Marketing and Purchasing: Which Interfaces to Improve the Value Creation Process? - Merminod, Nathalie; Fenneteau, Hervé; Pache, Gilles (Journal of Research in Marketing (ISSN: 2292-9355), 2017)
Processes for creating customer offerings, and, more broadly, processes for value creation, systematically lead to underline the importance of collective inter-firm action, particularly from a supply chain perspective. Without questioning the relevance of these approaches, the paper highlights that the management of intra-organizational interfaces should now be precisely understood to support inter-organizational approaches. More precisely, it strives to fill in a gap in supply chain research by developing the role of intra-organizational coordination of marketing, logistics and purchasing to improve the customer value. An exploratory research is done on relationships that link logistics, marketing and purchasing. The nature and difficulties of interfaces are analysed in order to identify key factors of improvement.